Jamblang (Syzygium cumini (L.)): A Review of Its Flower and Medicinal Uses - Khusniyah; Muthia Oktaviani Rahayu; Nayla Robiatul Adawiyah; Himyatul Hidayah (HM Publisher, 2023)
The Jamblang flower is a part of the plant that rarely gets attention in the process of exploring its properties. Jamblang flower is a part of the plant that is quite rich in antioxidant compounds. Antioxidants help protect the body's cells from oxidative damage and can help prevent various degenerative diseases such as heart disease, cancer, and premature aging. This study aimed to carry out a systematic review regarding the potential of Jamblang flowers (Syzygium cumini) in medicinal uses. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the potency of Jamblang flower (Syzygium cumini) in medicinal uses. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Jamblang flowers have interesting potential health benefits. The active compounds contained in Jamblang flowers, including antioxidants, anti-inflammatory compounds, and anticancer compounds, can provide health benefits for the body.